Ideals and institutions: Systemic reasons for the failure of a social forestry program in south-west Bangladesh. (December 2016) - Afroz, Sharmin; Cramb, Rob; Grünbühel, Clemens
Highlights: The Social Forestry Program failed to improve the livelihoods of the poor in southwest coastal Bangladesh. Formal and informal institutions combined to frustrate the ideals of Community-Based Natural Resource Management. The local context was much more complex than assumed by the project planners. Improving rural livelihoods and natural resource management will require far more transformative change. Abstract: We explore the contradictions between the ideals and principles of Community-Based Natural Resource Management (CBNRM) and the local-level institutional processes encountered in their implementation. In particular, we examine the design, implementation, and outcomes of the Social Forestry Program (SFP) in the south-west coastal region of Bangladesh through case studies of two villages in Khulna District. The SFP was a component of the donor-funded Sundarban Biodiversity Conservation Project (SBCP), intended to improve the livelihoods of poor households and protect the landscape through strip plantations on both sides of the large embankments that surround the farming land in the coastal region. Our findings show the gap between the national and international context in which the SFP was formulated and the realities of the local context in which formal and informal institutions worked to frustrate the achievement of CBNRM ideals. Hence the SFP failed to significantly increase forest cover or improve the livelihoods of the target populations. We document the specific ways in which the SFP deviated from the assumptions of CBNRM. However, we conclude that the problem is systemic, related to the top-down imposition of a supposedly bottom-up process, and not simply a matter of improving project implementation. Thus improving rural livelihoods and natural resource management in complex marginal environments such as south-west coastal Bangladesh will require far more transformative institutional change than can be achieved by donor-initiated project interventions, no matter how worthy the ideals.